Re-imagining Chemistry Laboratory Experiments by using Natural Pigments– Fostering Chemistry Students towards Sustainability - Das, S. S.; Bhagawati, B. (Journal of Scientific Research, 2024)
Green Chemistry and Sustainability are the two widely used concepts in the present-day Higher Education Chemistry curriculum. This paper issues a call for action for chemistry instructors to build stronger connections in the chemistry curriculum to sustainability. An acid-base titration is a commonly used experiment in undergraduate laboratories where synthetic indicators are generally used to locate the endpoint by observing the color change. In this paper, the ability of aqueous extracts of Lagerstroemia speciosa (locally known as Azar) as a natural indicator was investigated by using it instead of commonly used synthetic acid-base or neutralization indicators like Phenolphthalein, Methyl Orange, etc. The natural acid-base indicators are non-toxic, easily available, cost-effective, and environmentally benign. This inquiry-based investigation project can raise the standard of chemistry education while preserving local resources that can be used to address today's sustainability challenges. Thus, by considering several interconnected challenges to identify sustainable solutions that can be adopted in both higher secondary school and undergraduate chemistry education, such studies will enrich students' understanding of chemistry.